Resilience affecting the recurrence rate of schizophrenia patients in health community centre, Gamping 2, Sleman, Yogyakarta - Fiki Aji Nurcahyati; Rosma Fyki Kamala; Mulyanti Mulyanti (Alma Ata University Press, 2021)
Background: The rate of recurrence level in schizophrenia patients is still high. Schizophrenic patients experience various decreases in cognitive, emotional, social behavior, and brain functions, so that an optimal attitude of resilience is needed. Schizophrenic patients with good resilience can reduce the risk of recurrence.Objectives: The aim of this study is to analyze the relationship between resilience and recurrence rate of schizophrenia patients in Health Community Centre, Gamping 2, Sleman.Methods: This research was a quantitative research with a cross sectional design. Sampling technique used is simple random sampling. There were 44 schizophrenic patients for the sample in Health Community Centre, Gamping 2, Sleman, Yogyakarta. The instrument used was demographic data to measure recurrence, the CD-RISC10 questionnaire with the Kendall Tau test.Results: This research was a quantitative research with a cross sectional design. Sampling technique used is simple random sampling. There were 44 schizophrenic patients for the sample in Health Community Centre, Gamping 2, Sleman, Yogyakarta. The instrument used was demographic data to measure recurrence, the CD-RISC10 questionnaire with the Kendall Tau test.Conclusions: There is a relationship between resilience and recurrence on schizophrenia patients in Health Community Centre, Gamping 2, Sleman